Skin Color, Cultural Capital, and Beauty Products: An Investigation of the Use of Skin Fairness Products in Mumbai, India - Shroff, Hemal; Diedrichs, Phillippa C.; Craddock, Nadia (Frontiers in Public Health, 2018)
The use of skin fairness products that frequently contain toxic ingredients is associated with significant adverse health side effects. Due to the high prevalence of use in Asian and African countries, skin fairness product use is recognized as a growing public health concern. The multi-million-dollar skin fairness product industry has also been criticized for perpetuating racism and social inequalities by reinforcing beliefs about the benefits of skin fairness for cultural capital. No quantitative studies have assessed people’s beliefs about fairness and reasons for using or not using these products in India, one of the largest global markets for skin fairness products. The current study explored skin fairness product use among 1,992 women and men aged 16–60 years in the city of Mumbai, India using a self-report questionnaire. A total of 37.6% of the sample reported currently using skin fairness products, with women being two times more likely to use these products. Among current users, 17% reported past experiences of adverse side effects, and “Media/TV/Adverts” were the most common prompts for using fairness products, followed by “Friends” and “Family.” Men were significantly more likely than women to endorse beliefs about fairness being more attractive and were more likely to perceive family and peers as viewing fairness as beneficial for cultural capital. There were no differences between women and men currently using products in their desire to look as fair as media celebrities. Among non-users, women were significantly more likely than men to report concerns about product efficacy and side effects as reasons for non-use, while men were significantly more likely to report socioeconomic reasons for non-use. Implications of these findings are discussed in light of growing public health concerns about the use of fairness products, and potential for advocacy and public health interventions to address the use of skin fairness products.